Human Tendon Stem Cells Better Maintain Their Stemness in Hypoxic Culture Conditions - Zhang, Jianying (Public Library of Science, 2013)
Tissues and organs in vivo are under a hypoxic condition; that is, the oxygen tension is typically much lower than in ambient air. However, the effects of such a hypoxic condition on tendon stem cells, a recently identified tendon cell, remain incompletely defined. In cell culture experiments, we subjected human tendon stem cells (hTSCs) to a hypoxic condition with 5% O(2), while subjecting control cells to a normaxic condition with 20% O(2). We found that hTSCs at 5% O(2) had significantly greater cell proliferation than those at 20% O(2). Moreover, the expression of two stem cell marker genes, Nanog and Oct-4, was upregulated in the cells cultured in 5% O(2). Finally, in cultures under 5% O(2), more hTSCs expressed the stem cell markers nucleostemin, Oct-4, Nanog and SSEA-4. In an in vivo experiment, we found that when both cell groups were implanted with tendon-derived matrix, more tendon-like structures formed in the 5% O(2) treated hTSCs than in 20% O(2) treated hTSCs. Additionally, when both cell groups were implanted with Matrigel, the 5% O(2) treated hTSCs showed more extensive formation of fatty, cartilage-like and bone-like tissues than the 20% O(2) treated cells. Together, the findings of this study show that oxygen tension is a niche factor that regulates the stemness of hTSCs, and that less oxygen is better for maintaining hTSCs in culture and expanding them for cell therapy of tendon injuries.